Systems approach in the world heritage site Bahá’í Gardens - Jere Jakulin, Tadeja (Academica turistica, 2023)
The Bahá’í religion is the world’s youngest religion, founded in 1863 by the Persian sage Baha’u’llah. Its followers, including its founder, were persecuted for over a century until they found peace in the 21st century. Its two centres in Haifa, Israel, became UNESCO World Heritage Sites in 2008. The research aims to put the principles of systems thinking into practice in the case of the conservation of the Bahá’í Gardens, a World Heritage Site. The data for the causal-loop model (CLD) within the system dynamics framework, which we present in this paper, was obtained through a field survey of leaders of the Bahá’í religion. The theoretical models followed by a practical demonstration of the functioning and management of the Bahá’í Gardens in harmony with the social environment, the natural surroundings, pilgrims, and tourists, which illustrates the interplay between theory and the practical application of systems thinking for the highest good of world heritage and tourism. The research goes further by presenting, through the literature, the possibility of integrating religion and science, which as independent systems, are linked by a systems approach. The essence of Bahá’í thought is compassion, equality of races, interdependence, harmony, and living aesthetics and symmetry. All these elements fit into the modern systems’ principles, where systems cannot work until all their interdependent elements are balanced. The feedback loop and one’s awareness of it bring balance to the system, which presents the systems approach as a valuable tool in modern science.
Keywords: Bahá’í Gardens; Bahajski vrtovi; cldm odelling; pilgrimage tourism; romarski turizem; sistemski pristop; svetovna dediščina; systems approach; UNESCO; world heritage site